Aplikasi Sistem Informasi Keputusan Pemilihan Kualitas Komoditas Kopi Unggulan menggunakan metode Topsis - Hartanti, Dian; Mugiarso; Kusdarnowo; Nabilah, Tsamarah; Rasim; Noe'man, Achmad (Fakultas Teknik, Universitas Bhayangkara Jakarta Raya, 2025)
Currently, there is limited research focused on providing tools or systems for business owners to facilitate the quality determination of the coffee beans they use. However, quality coffee beans must be accurately identified based on proven standards and criteria. Unfortunately, coffee quality determination is still often done visually or by manual observation, practices that risk compromising the accuracy of the final product's quality and flavor. To ensure the selection of superior coffee beans, a structured decision-making mechanism is required. The solution is a Decision Support System (DSS), a computer information system that is adaptive, interactive, and flexible. This development research applies the Topsis (technique for order preference by similarity to ideal solution) method, to determine the results of calculations for superior coffee bean selection.